Panitikan a documentary on American colonial and contemporary traditions in Philippine literature - Mojares, Resil B.; Lucero, Rosario Cruz; Diokno, Ronald Antonio (Tuklas sining series, 1993)
Shows the wealth of Philippine literature produced during the American colonial period up until the Martial Law period.